KEANEKARAGAMAN JENIS GULMA BERDAUN LEBAR PADA PERTANAMAN JAGUNG (Zea mays L.) DI DESA SANGATTA SELATAN KABUPATEN KUTAI TIMUR - Rusdi Rusdi; Zainuddin Saleh; Ramlah Ramlah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Behind this study is diversity of Broadleaf Weed Species in corn plantation. The aims of this research to determine the Diversity of Broadleaf Weed Species at corn (Zea mays L.) plantation, at Desa Sangatta Selatan, Kabupaten Kutai Timur.This research used a square method, which is manufacture of plots with a zise 2 x 2 m as much as 9 plots. Weeds found in the plot were identified and subsequently performed the calculation of aech species in each plot. The results showed that founded 11 species in 10 families. The highest dominance value in sequence, that is: Hedyotis corymbosa L. (28,03%), Phyllantus niruri Klein ex Willd. (16.97%), Ageratum conyzoides L. (12.40%). and the lowest are: Hyptis capitata Jacq. (1,59%). Weed diversity is heterogeneous, which means there is no one Broadleaf Weed Species was the dominance value of more than 80%. Further research required regarding diversity grass weed classes and nut grass was founded on corn plantation in a wider scale and the effect on corn production.